Inhaled Methane Limits the Mitochondrial Electron Transport Chain Dysfunction during Experimental Liver Ischemia-Reperfusion Injury. - Gerda Strifler; Eszter Tuboly; Edit Szél; Enikő Kaszonyi; Chun Cao; József Kaszaki; András Mészáros; Mihály Boros; Petra Hartmann (PLoS ONE, 2016)
BACKGROUND:Methanogenesis can indicate the fermentation activity of the gastrointestinal anaerobic flora. Methane also has a demonstrated anti-inflammatory potential. We hypothesized that enriched methane inhalation can influence the respiratory activity of the liver mitochondria after an ischemia-reperfusion (IR) challenge. METHODS:The activity of oxidative phosphorylation system complexes was determined after in vitro methane treatment of intact liver mitochondria. Anesthetized Sprague-Dawley rats subjected to standardized 60-min warm hepatic ischemia inhaled normoxic air (n = 6) or normoxic air containing 2.2% methane, from 50 min of ischemia and throughout the 60-min reperfusion period (n = 6). Measurement data were compared with those on sham-operated animals (n = 6 each). Liver biopsy samples were subjected to high-resolution respirometry; whole-blood superoxide and hydrogen peroxide production was measured; hepatocyte apoptosis was detected with TUNEL staining and in vivo fluorescence laser scanning microscopy. RESULTS:Significantly decreased complex II-linked basal respiration was found in the normoxic IR group at 55 min of ischemia and a lower respiratory capacity (~60%) and after 5 min of reperfusion. Methane inhalation preserved the maximal respiratory capacity at 55 min of ischemia and significantly improved the basal respiration during the first 30 min of reperfusion. The IR-induced cytochrome c activity, reactive oxygen species (ROS) production and hepatocyte apoptosis were also significantly reduced. CONCLUSIONS:The normoxic IR injury was accompanied by significant functional damage of the inner mitochondrial membrane, increased cytochrome c activity, enhanced ROS production and apoptosis. An elevated methane intake confers significant protection against mitochondrial dysfunction and reduces the oxidative damage of the hepatocytes.